Impact of wind shear on aerosol–cloud interactions and convective precipitation - Tonn, Mathis; Barthlott, Christian; Kunz, Michael; Hoose, Corinna (Frontiers in Environmental Science, 2025)
The impact of wind shear on aerosol-cloud interactions and convective precipitation is investigated with real-case simulations using the ICOsahedral Non-hydrostatic (ICON) model over central Europe. Three days with severe convective storms have been simulated using a double-moment microphysics scheme on a 1-km grid. For each day, twenty simulations with varied initial vertical wind shear and cloud condensation nuclei (CCN) concentrations were performed. In these simulations, a higher convective potential is found for stronger wind shear. However, this is not necessarily reflected in the amount of precipitation, which shows no systematic dependency on the wind shear for the days analyzed. Changing the CCN concentration generally has a smaller impact on the precipitation amount than changing the wind shear. Even if hydrometeor amounts and microphysical process rates respond similarly to changing CCN concentrations in the different shear cases, the convective precipitation shows no systematic CCN dependency. Furthermore, it is shown that this dependency even changes for a different simulation duration. If the amount of precipitation is related to its generation processes, a systematic relationship emerges: the precipitation efficiency always increases with increasing CCN concentrations, and this increase is greater the higher the initial wind shear of the simulations is. The findings of the present paper demonstrate that the impact of wind shear on aerosol-cloud interactions is complex, and previous results from idealized simulations cannot be transferred to realistic simulations.